A PDA-based teleoperation interface to control ATRV robots and simulated robots - Li, Hongbin. (2009)
Since the first telerobotic system was deployed for handling radioactive materials in 1940s, numerous tasks that were once undertaken by human beings are performed by telerobots. Nowadays, telerobotics has turned to be one of our most influential technologies. To enable the interaction between human beings and robots, researchers employed various platforms to build interfaces. Being inexpensive, small, portable, and fairly easy to use, Personal Digital Assistants (PDAs) have convinced many as an attractive device. The objective of this project is to develop a PDA-based teleoperation interface that is able to control multiple mobile robots from different robotics systems, i.e. All-Terrain Robot Vehicle (ATRV) robots and simulated robots, with varying degree of autonomy. A PDA device is chosen as the platform of the interface system with the prime consideration that human controller can control and monitor the behavior of robots with assistance from a portable interface. Simulated robots are created in a 3D virtual environment—Robotics Simulator. Performing experiment in simulator is recognized as a safe, cost effective, time saving solution to study Human Robot Interactions (HRI).